(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Principal leadership is a person’s ability to influence, guide, encourage, mobilize and direct other people in terms of learning and can carry it out effectively. This research aims to examine the influence of the Principal’s Transformational Leadership on teacher performance, the influence of work motivation on the performance of junior high school teachers in Sinaboi District, Rokan Hilir Regency. This type of research is quantitative descriptive research and survey methods with correlational research techniques. The data collection technique used was a questionnaire with 62 junior high school respondents in Sinaboi subdistrict, Rokan Hilir Regency who were selected using a sampling technique using Total Sampling. The research method used is that respondents provide responses to the questionnaire in the form of a Likert scale consisting of five answer choices, namely Strongly Agree, Agree, Undecided, Disagree, and Strongly Disagree. The data analysis used is descriptive and inferential statistics. Based on data analysis, it was found that the positive influence of the Principal leadership variable on the Performance of Middle School Teachers in Sinaboi District, Rokan Hilir Regency was 34.4%, while the remaining 65.6% was determined by other factors which were not part of this research; Furthermore, it was found that the positive influence of the work motivation variable on the performance of junior high school teachers in Sinaboi District, Rokan Hilir Regency was 21%, while the remaining 79% was determined by other factors which were not part of this research; and it was found that the positive influence of the Principal leadership variable and Teacher Work Transformation on Middle School Teacher Performance in Sinaboi District, Rokan Hilir Regency was 44.6%, while the remaining 55.4% was determined by other factors which were not part of this research.